"Kriegs-Urkunden-Sammlung" (Urkunden zur Geschichtsschreibung) : Sammlungen der offiziellen bekanntmachungen vom 1. Mobilmachungstage, den 1.8. 1914 bis zum Waffenstillstand und Ausbruch der deutschen Revolution den 9. November 1918 - Archiv-Dienst Karl Engelmann; Engelmann, Karl (1914)
Collection of official notices and ephemera related to World War I from mobilization on August 1, 1914 until the armistice and outbreak of the German Revolution on November 9, 1918.
Title from typewritten list of contents.
NUC pre-1956
Keywords: World War, 1914-1918 -- Germany; World War, 1914-1918 -- Sources; World War, 1914-1918 -- Posters; Political posters, German; Broadsides -- Germany; Posters -- German -- 1910-1920.